Beyond the Numbers: Quantitative and qualitative analysis of quality of life after deep brain stimulation for OCD - Emily Hemendinger; John A. Thompson; Jennifer Fishman; Katie Sinsko; Hannah Gebhardt; Rachel A. Davis (PLoS ONE, 2026)
Purpose Obsessive-Compulsive Disorder (OCD) severely impairs quality of life (QoL) in many sufferers. Deep Brain Stimulation (DBS) can be effective therapy for OCD that is refractory to standard treatment options, which include medications and cognitive behavioral therapy/exposure and response prevention therapy. The purpose of this study was to acquire qualitative data about the impact of DBS on QoL for people who have treatment refractory OCD. Methods Ten subjects who received DBS surgery and are receiving ongoing DBS programming participated in this study. Pre- and post-surgery assessments (Q-LES-Q-SF and Y-BOCS) were analyzed for 8 of the 10 participants, and narratives from all 10 subjects were coded for themes. To assess individual correlations, analyses were completed within each participant, using solely their data points. Results In six out of 8 subjects, improved QoL scores correlated with a decrease in Y-BOCS score, although this was only found to be significant in 2 of the 6 subjects. Qualitative data revealed that pre-DBS QoL was generally poor, with patients experiencing impairment in at least one domain. Post-DBS, most patients described improvements in overall QoL, particularly in the areas of mood and general functioning. However, many continued to experience difficulties in the social/relationship domain, including difficulty with social skills and transition to independent living. Conclusions These findings suggest that focused interventions addressing social skills and independent living may enhance post-DBS quality of life.